2020
DOI: 10.2478/fon-2020-0037
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the nurses’ intent to stay in China, Japan, and Korea: an integrative review

Abstract: ObjectiveNurse's dimission and attrition are globally considered as a public health issue. However, few studies have focused on the nurse shortage from the perspective of intent to stay, as previous studies have focused only on why they left. The purpose of this study was to conduct an integrative review of the factors connected with why nurses in China, Japan, and Korea stay in their current workplace.MethodsThe review was done using three databases namely CNKI, Wanfang, and Web of science. The relevant studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The findings were consistent with those of Xue et al. (2020), who revealed that transformational leadership by nurse managers improved nurses’ intent to stay within their healthcare setting. Similarly, Wang et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings were consistent with those of Xue et al. (2020), who revealed that transformational leadership by nurse managers improved nurses’ intent to stay within their healthcare setting. Similarly, Wang et al.…”
Section: Discussionsupporting
confidence: 91%
“…The result showed that transformational leadership positively affected intent to stay, indicating that nurses' perceptions of transformational leadership displayed by their head nurses improved their intent-to-stay level. The findings were consistent with those of Xue et al (2020), who revealed that transformational leadership by nurse managers improved nurses' intent to stay within their healthcare setting. Similarly, Wang et al (2018) revealed that intent to stay among registered nurses in Shanghai, China, was directly influenced by the transformational leadership style of nurse managers (β = 0.36, p = 0.000).…”
Section: Discussionsupporting
confidence: 87%
“…al, 2017;Lorenzo et al, 2007). A review study identified three main contributing factors of nurses' intent to stay: nurses' individual characteristics, professional characteristics, and organizational factors (Xue et al, 2020). At this backdrop, steps must be made in preventing high turnover rates of nurses and maintaining a committed nursing workforce (Labrague et.…”
Section: Introductionmentioning
confidence: 99%
“…However, the scarcity of nursing personnel is a global challenge [3] . As of the end of 2021, China's total number of registered nurses reached 5,018,000 (3.56 registered nurses per 1,000 population), significantly lower than the World Health Organization's recommended ratio of 4.45 registered nurses per 1,000 population [4] .…”
Section: Introductionmentioning
confidence: 80%